Study of electronic interactions and photo-induced electron transfer dynamics in a metalloconjugated polymer–single-walled carbon nanotube hybrid by ultrafast transient absorption spectroscopy. Issue 35 (17th August 2017) - Shi, Haiting; Du, Lili; Xiong, Wenjuan; Dai, Mingjie; Chan, Wai Kin; Phillips, David Lee
Abstract : The present study demonstrated the selective dispersion of SWCNTs by the metalloconjugated polymer, and the evidence of electron injection from the sensitizers to SWCNTs. Abstract : Regioregular poly(thiophene) functionalized with pendant photosensitizing ruthenium complexes was synthesized. The conjugated polymer serves dual functions as a dispersant for single-walled carbon nanotubes (SWCNTs) and also as a photosensitizer. SWCNTs can be dispersed effectively by the polymer, and the polymer/SWCNT hybrid dispersion obtained was stable for months. Raman spectroscopic results showed that there was no structural damage or defects present in SWCNTs after the functionalization process and SWCNTs with both small (0.9 nm) and large (1.6 nm) diameter can be dispersed. Transmission electron microscopy revealed the presence of polymers on the SWCNT surface. The dynamics of the photo-induced electron transfer process between the ruthenium sensitizers and SWCNTs was probed by femtosecond transient absorption spectroscopy. Rapid electron injection from the ruthenium sensitizers to SWCNTs with a time constant of 167 ps was observed. By using this synthesis approach, it is possible to incorporate different types of sensitizers in one polymer chain so as to fine-tune the absorption spectra, and a new light harvesting system can be developed by coupling the polymer with SWCNTs.